Pengembangan E-Module Struktur Atom dan Nanoteknologi menggunakan Flip Pdf Professional - Ade Islamiati; Yanti Fitria; Elfia Sukma; Yaswinda; Elwil Fitria; Siska Tresia Oktari (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to investigate the effect of using the Problem-Based Learning (PBL) model and variations in learning styles on the critical thinking abilities of class IV students in Cluster V, Palembayan District. Critical thinking ability is a key skill in modern education, encouraging the development of analytical, evaluative and reflective thinking. The research method used in this research is a quasi-experiment with a research design using an experimental design with a 2x2 factorial design technique where there will be a control class and an experimental class. The research sample consisted of two groups of class IV students, one experimental group taught using the Problem-Based Learning (PBL) model and one control group taught using a conventional approach. In addition, student learning styles were also identified and analyzed in this research. The research results showed that the group of students taught using the Problem-Based Learning (PBL) model experienced a significant increase in critical thinking skills. This is reinforced by the results of statistical analysis which show that the value of tcount (1.910) is higher than ttable (1.708) at a significance level of 0.05. Therefore, it can be concluded that the Problem Learning (PBL) model has a positive effect on increasing students' critical thinking skills. Apart from that, this research also identified that student learning styles influence learning outcomes. Some learning styles may be better suited to a PBL approach, while others are better suited to a conventional approach. Therefore, educators are expected to consider variations in student learning styles in designing effective learning.